Case Reports of Cow's Milk Protein Allergy Presenting as Delayed Passage of Meconium With Early Onset Infant Constipation - Madala, Akshita; Lure, Allison C.; Cheng, Svea; Cheng, Sam X. (Frontiers in Pediatrics, 2022)
Cellular proliferation to milk allergens has been found in cord blood cells of neonates. While this reflects a sensitivity during fetal life, its clinical significance and disease, particularly its unconventional presentations have remained largely unrecognized by care providers. Here, we report three cases of infants whose mothers consumed dairy products during pregnancy, who developed a severely constipated pre- and post-natal bowel. The passage of meconium was significantly delayed with subsequent early onset infant constipation that was intractable to conventional therapies but remitted when milk proteins were withheld, recurred when milk proteins were reintroduced, and resolved again when switched to an extensively hydrolyzed or an amino acid based infant formula. Based on this and other observations, it is believed that these infants must have initiated and/or developed cow’s milk protein allergy prenatally during fetal life. We suggest that a two-week trial of cow’s milk protein avoidance be applied to these neonate infants with early onset constipation before an unnecessary invasive work up for Hirschsprung disease and others is initiated per current guidelines.